The Effect of Using Weightlifting Exercises on Some Biomechanical Variables and the Level of Technical Performance of Shooting by Jumping in Basketball - Rashid Saeed, Mahmood; Khalid Humadi, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study was to prepare exercises with weights for the development of some biomechanical variables for the individuals of the research sample, and also to identify the effect of exercises for weights in the research variables of the research, as the researcher used the experimental approach to its suitability to solve the research problem, as the design of the one group with pre- and posttests was chosen, and the research sample formed One of the basketball players for Al-Wahda Sports Club, with 5 players out of 15, who represent the only experimental group in researching and using the appropriate tools and devices. The exploratory experiment was conducted, and then the pretests were conducted for the group. After that, we applied the exercises of weightlifters, then conducted post-tests for them, then emptied and statistically processed the data, displaying, analyzing, and discussing them. The researcher reached several conclusions, which are 1. The exercises with weightlifting prepared by the researcher after their application positively affected the development of some biomechanical variables among the individuals of the experimental research sample. 2. That the gradient and diversity in the training load of weight training exercises prepared by the researcher had a positive effect in developing some biomechanical variables among the individuals of the experimental research sample.